X-ray Crystal Structure of Dichromium-transferrin with Synergistic Anion Malonate (P24-061-19). (13th June 2019) - Vincent, John; Edwards, Kyle; Petersen, Courtney; Gilbert, Nathaniel; Thompson, Matthew
Abstract: Objectives: Transferrin, Tf, the protein that transports iron, as Fe(III) from the blood to the tissues via endocytosis, is believed to also transport chromium(III), Cr(III). Under physiological conditions, transferrin binds Fe(III) and Cr(III), but can bind other metal ions such as titanium(IV), Ti(IV), such as in the blood of patients with Ti-containing implants. Questions have arisen whether similar protein and non-protein ligands are bound to the alternative metal ions in transferrin. Methods: Human serum Cr(III)2 -Tf was prepared in a buffered solution at pH 7.4 containing 25 mM bicarbonate at 37°C. The hanging drop vapor diffusion method was used for crystallization. The crystallization conditions contained 100 mM Hepes (pH 7.0, 20 mM disodium malonate, 14% PEG3350, 20% glycerol, and 55 mg/mL transferrin. Results: Cr(III)2 -Tf crystallized in the space group C2221 with unit cell dimensions a = 137.05 Å, b = 158.01 Å, and c = 107.14 Å and α = β = γ = 90°. The C-terminal lobe is in the closed confirmation, while the N-terminal lobe is in the open confirmation. The C-terminal metal-binding site has four protein-provided ligands (two tyrosines, one histidine, and one aspartate) to the Cr(III) center, while six coordination is completed by two oxygens from a malonate anion. Thus, under the crystallization conditions, malonate displaces `the synergistic bicarbonate anion normally at the metal-binding site. The N-terminal metal binding site possesses only one protein-provided ligand (tyrosine) while the other binding sites about the Cr(III) center are filled by a (bi)carbonate anion and water molecules. Conclusions: Under the conditions of crystallization, the C-terminal lobe of transferrin binds Cr(III) in a similar fashion to Fe(III) and Ti(IV), although the ligation at the N-terminal binding site varies. These similarities and differences in coordination have implications for the relative ability of transferrin to bind and release Fe, Cr, and Ti. Funding Sources: The University of Alabama College of Arts and Sciences Research Award.